Histoire de l'Internationale Socialiste - Engels, Friedrich; Kautsky, Karl; Vandervelde, Emile; Adler, Friedrich; Bauer, Otto (Bruxelles: L'Églantine, 1924)
"F. Engels, K. Kautsky, E. Vandervelde, O. Bauer, Fr. Adler Fonds Perrone"